Properties and application possibilities of wheat bran proteins - Chaquilla-Quilca, Guadalupe (Universidad Autónoma de Tamaulipas, 2018)
Wheat bran is mainly intended for animal consumption and some of its components are underutilized, representing value-added opportunities. It forms the outer layers of the grain and contains up to 18 % by weight of proteins of better quality than those of flour. These proteins are not exploited because most are protected by a matrix of polysaccharides, which is indigestible by the human gastrointestinal system, so their extraction is necessary. Traditionally, wheat bran proteins have been recovered by alkaline extraction and have been proposed as ingredients for the manufacture of foodstuffs. However, their use is almost non-existent because the extraction processes are aggressive and not profitable. The aim of the present review is to present the properties of wheat bran proteins, as well as, their potential uses. Among their properties, the digestibility, lipid absorption capacity and aminoacid pattern are highlighted. The water soluble fraction of these proteins, because of their easy extraction, could have an added value from the perspetive of emerging technologies, for example, as a source of bioactive peptides, in the production of nanoparticles with industrial applications or as matrices for artificial biomineralization processes.